Knowledge Creation Through Mobile Social Networks and Its Impact on Intentions to Use Innovative Mobile Services - Kleijnen, Mirella; Lievens, Annouk; de Ruyter, Ko; Wetzels, Martin (Journal of service research : JSR, 2009)
Taking a social network perspective, the authors investigate consumers' intentions to use innovative mobile services. With a sociometric survey, they empirically assess how consumers integrate and connect through mobile social networks, as well as how their network position influences knowledge creation and intentions to use four innovative mobile services: multimedia messaging, gaming, information, and transactions. Both personal (i.e., opinion leadership and experience with the communication mode) and similarity attributes of social network members have a significant impact on network position, that is, their level of individual connectedness and integration. In addition, the impact of this network position on knowledge creation is contingent upon the type of innovative service. In three out of four mobile service categories, integration exhibits a negative effect on knowledge creation, whereas connectedness has a positive effect. Knowledge creation significantly influences intentions to use mobile services. Moreover, the authors demonstrate that carryover effects occur across the four service categories. Finally, the network's perceived ability to adopt innovative mobile services has a different impact on usage intentions across the four service categories.